Nimesulide: A double-edged sword must be banned - Bin Khalid, Muhammad Moaz; Muhammad Nouman (Journal of the Pakistan Medical Association, 2023)
Dear Editor, My purpose in writing this letter is to draw your attention to a very susceptible situation of possible adverse reactions like hepatotoxicity caused by Nimesulide. It is being prescribed as an over-the-counter drug and is available even online for home delivery without any prescription in Pakistan. Nimesulide is an atypical selective COX-2 inhibitor that is similar in anti-inflammatory effects as compared to other classical NSAIDs and selective COX-2 (celecoxib & rofecoxib) inhibitors but different as it has a protective effect on NSAID-induced ulcers as compared to other more selective COX-2 inhibitors, which do prevent but do not protect NSAID induced ulcers. But, does this only benefit of being gastroprotective justify its use as a relatively common drug with or without a prescription? —Continue